Analisis Peningkatan Kemampuan Public Speaking Dari Menonton K-Drama Bagi Siswi SMA Negeri No 09 Palembang - Windy; Achmad Syarifudin; Manalullaili (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
Korean culture called Hallyu has produced many products such as movies, music, food, drama series, fashion and lifestyle. These Hallyu products spread all over the world with thedevelopment of science and technology. Therefore, through research, researchers have problems with the type of Korean language that can be used as a style of speaking in public when watching Korean dramas according to the scriptwriter's direction and inclination. This research is entitled "Analysis of Increased Public Speaking of SMA N 09 Palembang Students from Watching K-dramas" This study aims to find out how the Public Speaking Ability of female students before watching k-dramas, Why do SMA N 09 Palembang students like k-drana, and is there any impact from watching k-dramas on students' Public Speaking abilities. This research uses the Uses and Gratifications Theory. Consists of Observations, Interviews, and Documentation. Based on the results of the research that have been described, it can be concluded that the Public Speaking Ability of Students Before Watching K-dramas is Ordinary. Why do SMA N 09 Palembang students like k-drama so much because the storyline is very interesting, from a unique background story and Korean language is exciting with its accent or intonation and don't forget the actors and actresses who are very handsome and beautiful so that many teenagers, especially SMA N students 09 Palembang who really liked the drama.And is there an impact of watching K-drama on the student's public speaking ability from the statement from the results of the interview? Some of them have improved and some are mediocre. In terms of speaking style, many can learn Korean from watching Korean drama shows, this is related to Typology of Uses and Gratifications by Rubin (1981) where the reason for using media is to get information, learn about material, this is related to the increase in public speaking of the SMA N 09 Palembang students.